Transformasi Pedagogis Guru IPA: Implementasi Lokakarya Deep Learning untuk Pemberdayaan Keterampilan Abad 21 - Neni Hasnunidah; Tri Jalmo; Dewi Lengkana; Chansyanah Diawati; Pramita Sylvia Dewi (Ruang Pengabdian: Jurnal Pengabdian kepada Masyarakat, 2025)
Curriculum transformation requires science teachers to master innovative learning design, but competence in applying Deep Learning approaches and 21st century skills assessment remains a challenge. This service aims to improve the understanding of junior high school/MTs science teachers about the philosophical foundations of deep learning, curriculum analysis and essential science content to support in-depth science learning, design science learning with a deep learning approach, and design a deep learning-oriented science learning assessment that integrates 21st Century Skills and SDGs issues. This activity was carried out using a participatory and reflective workshop method to 30 science teachers Junior High School/MTs which are members of the Subject Teacher Conference of Pringsewu and South Lampung Regencies. Program evaluations use the CIPP model that measures competency improvement through context, input, process, and product analysis. The results of the activity showed a significant increase in the understanding of the workshop participants. The final test results with good criteria on all training materials increased by 64.75% from the initial test results with poor criteria. The response of the participants was very positive with an average of 60% stating that this activity was beneficial and improved their professionalism. The workshop was shown to be effective in supporting teachers' pedagogical transformation, with the implication that similar approaches can be replicated for sustainable professional development on a wider scale.